The effect of planting media and seed soaking on the growth of true shallot (Allium ascalonicum L.) seeds - Putri, Kansa Dianti (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The Shallots are one of the commodities in high demand in Indonesia. One method for increasing shallot growth is to use good planting media and seed treatment. The purpose of this experiment was to see what effect planting media and seed soaking had on the growth of shallot TSS (Allium ascalonicum L.). A factorial randomized block design (RAK) with three replications was used in the experiment. The first factor is the planting media, which is divided into three levels: M1 (cocopeat), M2 (zeolite), and M3 (sand). The second factor is seed soaking, which has three levels: no soaking (P0), warm water 35°C 30 minutes (P1), and plain water 24 hours (P2). When compared to sand planting media, the treatment of cocopeat and zeolite planting media had a significant effect on germination capacity and fresh weight. Soaking shallot seeds in warm water at 35°C for 30 minutes and plain water for 24 hours had a significant effect on germination, plant height, number of leaves 7-21 DAT, fresh weight, and dry weight of shallots compared to not soaking. There is a significant interaction that affects the percentage of germination. However, there was no significant interaction between plant height, number of leaves, fresh weight, and dry weight of shallots and various planting media and seed soaking.